A Collective Institution Metamorphosed. The patriziati in the Ticino Alps Between Historical Heritage and New Functions - Luigi Lorenzetti; Roberto Leggero (Revue de Géographie Alpine)
This article analyses the institutional evolution and transformations of the functions of the Alpine patriziati of Canton Ticino, i.e. the collective institutions which have inherited some of the goods of the former rural communities and which currently own and continue to manage a large part of the forest and alpine pasture of this Swiss canton. As corporations under public law, the patriziati have been led to broadening their functions. They have integrated those related to environmental protection and ecosystem services in addition to those related to the economic exploitation of their undivided property. The analysis tries to verify how this evolution has been influenced by the financial conditions of the patriziati and in their activities. The results suggest that financially stronger corporations are better able to integrate these new functions, thus promoting the sustainable management of their assets. However, the abandonment of two regional park projects, rejected in two popular votes, shows that the diversification of the functions of the patriziati must be embedded in inclusion processes capable of bypassing rivalries in the use of their resources.